2019
DOI: 10.1021/acs.jpcc.8b12514
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Carrier Dynamics of Undoped and Ho3+-Doped α-Bismuth Oxide Microrods

Abstract: We report the femtosecond two-color pump–probe studies on bismuth oxide microrods. The undoped data show three distinct decays: (1) fastest decay (τ1 ∼ 0.3–0.5 ps) attributed to intraband nonlinear effects (2) intermediate two-body decay (τ2 ∼ 3 ps) attributed to the trap-assisted Auger recombination; and (3) slow single-body decay (τ3 ∼ 36 ps) attributed to the Shockley–Read–Hall recombination. Upon doping with Ho3+, the sample shows an additional slow decay (τ4 ∼ 12 μs), attributed to the Shockley–Read–Hall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 39 publications
3
6
0
Order By: Relevance
“…The (I2LO/I1LO) ratio was found to be 0.86 and 0.43 for NiO and Ni0.95E0.5O, respectively. The ease off in the coupling strength of Ni0.95E0.5O samples in comparison with pure NiO can be due to the reduction in phonon lifetime that arises due to the defects on the surface [52,53]. This observation is in accordance with the results obtained from XPS analysis.…”
Section: Raman Analysissupporting
confidence: 87%
See 2 more Smart Citations
“…The (I2LO/I1LO) ratio was found to be 0.86 and 0.43 for NiO and Ni0.95E0.5O, respectively. The ease off in the coupling strength of Ni0.95E0.5O samples in comparison with pure NiO can be due to the reduction in phonon lifetime that arises due to the defects on the surface [52,53]. This observation is in accordance with the results obtained from XPS analysis.…”
Section: Raman Analysissupporting
confidence: 87%
“…were observed in the Raman spectra, the intensity ratio of 1LO to 2LO (I2LO/I1LO) can be found to estimate the coupling strength [32,53,63]. The (I2LO/I1LO) ratio was found to be 0.86 and 0.43 for NiO and Ni0.95E0.5O, respectively.…”
Section: Raman Analysismentioning
confidence: 93%
See 1 more Smart Citation
“…The best fitting results (Table S4) show that the both kinetics present the similar decay trend (τ 2 and τ 4 ) for commercial In 2 O 3 and N–In 2 O 3 . However, an additional fast decay τ 1 (6.5 ps) is shown after N-doping, and it should be attributed from the doping-assisted trapping process. , It was reported that the electron-trapping process in semiconductors usually has a picosecond lifetime . Therefore, the 54 and 64 ps in both kinetics come from the electron trapping by shallow defect sites near conducting band.…”
Section: Resultsmentioning
confidence: 96%
“…However, an additional fast decay τ 1 (6.5 ps) is shown after N-doping, and it should be attributed from the doping-assisted trapping process. 90,91 It was reported that the electron-trapping process in semiconductors usually has a picosecond lifetime. 92 Therefore, the •− was an important active…”
Section: ■ Results and Discussionmentioning
confidence: 99%